System characterization and performance studies with MACACO III Compton camera. (July 2023) - Barrientos, L.; Borja-Lloret, M.; Casaña, J.V.; Hueso-González, F.; Ros, A.; Roser, J.; Senra, C.; Solaz, C.; Viegas, R.; Llosá, G.
Abstract: The IRIS group of IFIC-Valencia has developed a Compton camera prototype. The system detectors are made of Lanthanum (III) bromide scintillator crystals coupled to silicon photomultipliers. Two models of silicon photomultipliers arrays with different micro pixel pitch (25 and 50 μ m) have been chosen as possible candidates to improve the response of the new system. Characterization studies with a 22 Na point-like source have indicated that the 25 μ m photodetector provided better performance in terms of energy resolution (5.2% FWHM at 511 keV) and angular resolution (6.9 ∘ FWHM at 1275 keV), and more stability with temperature variations. In addition, MACACO III imaging capabilities have been assessed using a structure composed of thirty-seven 22 Na point-like sources. Furthermore, in order to evaluate possible ways of improving the system performance, several studies have been carried out by means of simulations both in realistic and performance improved conditions. In this work, the system performance is evaluated for its future application in different areas. Highlights: Compton camera prototype development with significant performance improvement. Better temperature and voltage stability with new photodetectors. Enhanced prototype imaging capability as a consequence of the detectors choice. Performance improvement studies through validated simulations. Estimation of system spatial resolution with Derenzo-like phantoms.